2006
DOI: 10.1016/j.polymer.2006.01.065
|View full text |Cite
|
Sign up to set email alerts
|

Continuity development in polymer blends of very low interfacial tension

Abstract: Continuity development in polymer blends of very low interfacial tension AbstractPhase continuity development and co-continuous morphologies are highly influenced by the nature of the interface in immiscible polymer blends. Blends of ethylene-propylene-diene terpolymer (EPDM) and polypropylene (PP) possess an interfacial tension of about 0.3 mN/m and provide an interesting model system to study the detailed morphology development in a very low interfacial tension binary system. A variety of blends with viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 53 publications
3
46
0
Order By: Relevance
“…The EPDM is evident as a red phase corresponding to a topographical valley of 30 nm. Note that although the EPDM appears to be dispersed in this 2-D micrograph, it is in fact fully co-continuous as confirmed by solvent gravimetry data in our previous article, 3 and also as shown later in Figure 7. For the purpose of further discussion, this co-continuous, noncrosslinked, 50 EPDM/50 PP morphology will be referred to as the "␣-network".…”
Section: Microstructure Of Crosslinked Blendssupporting
confidence: 85%
See 3 more Smart Citations
“…The EPDM is evident as a red phase corresponding to a topographical valley of 30 nm. Note that although the EPDM appears to be dispersed in this 2-D micrograph, it is in fact fully co-continuous as confirmed by solvent gravimetry data in our previous article, 3 and also as shown later in Figure 7. For the purpose of further discussion, this co-continuous, noncrosslinked, 50 EPDM/50 PP morphology will be referred to as the "␣-network".…”
Section: Microstructure Of Crosslinked Blendssupporting
confidence: 85%
“…The capability of combined FIB/AFM is clearly able to resolve the presence of very small EP domains. In an earlier publication, 3 using SEM analysis, we demonstrated that these dispersed domains are actually very fine diameter stable fibers. There is a good correlation between the phase size observed here and in that previous article.…”
Section: Microstructure Of Crosslinked Blendsmentioning
confidence: 55%
See 2 more Smart Citations
“…Due to the high specific surface area of nanoparticles, the anchoring of the polymer components on the solid nanoparticles is believed to thermodynamically stabilize nano-filled polymer blend systems [54]. Phase continuity development and co-continuous morphologies are highly affected by the nature of the interface in immiscible polymer blends [55]. In general, the mechanical and optical properties of immiscible polymers depend on the disperse phase morphology.…”
mentioning
confidence: 99%